Small extracellular vesicles derived from miRNA-486 overexpressed dental pulp stem cells mitigate high altitude pulmonary edema through PTEN/PI3K/AKT/eNOS pathway - Changyao Wang; Zhuang Mao; Drolma Gomchok; Xue Li; Huifang Liu; Jingyuan Shao; Hu Cao; Guanzhen Xue; Lin Lv; Junzhao Duan; Tana Wuren; Hua Wang (Heliyon)
High altitude pulmonary edema (HAPE) is a life-threatening, non-cardiogenic pulmonary edema characterized by rapid onset and high mortality. Extracellular vesicles of mesenchymal stem cells are used in the treatment of a variety of lung diseases, but their use in HAPE remains underreported. This study explores the therapeutic potential of miRNA-486 modified extracellular vesicles from dental pulp stem cells (sEVmiR−486) against HAPE, aiming to decipher the associated molecular mechanisms. The rat HAPE model was established by exposing subjects to a simulated high-altitude, low-oxygen environment within a specialized chamber. The HAPE-afflicted rats received sEVNull and sEVmiR−486 intravenously, and the therapeutic effect was assessed through histopathological analysis, pulmonary artery pressure, lung water content, as well as markers of oxidative stress and inflammation. To supplement in vivo findings, pulmonary microvascular endothelial cells (PMVEC) were stressed with cobalt chloride to emulate hypoxic damage, and then treated with sEVNull and sEVmiR−486 to unravel the mechanism of action. The sEVNull mitigated pathological changes in the lungs, reduced pulmonary artery pressure and lung water content, and alleviated oxidative stress and inflammatory responses in cases of HAPE. Moreover, sEVNull enhanced vascular reactivity and restored pulmonary permeability and tight junction integrity, these effects were intensified by miRNA-486 overexpression. Notably, sEVmiR−486 attenuated oxidative damage in hypoxic PMVEC cells by modulating the PTEN/PI3K/Akt/eNOS signaling pathway. miRNA-486 fortified DPSC-sEVs intervention as a novel and potent treatment strategy for HAPE.